Parliamentary Elite and Informal Institutions in Chile. Nepotism and Clientelism at the Basis of Political Power [Élite Parlamentaria E Instituciones Informales en Chile. Nepotismo y Clientelismo Como Formas de Sustento del Poder] - Espinoza-Espinoza, V (Federacion Espanola de Sociologia, 2020)
In 2015, scandals linked to party financing in Chile led to an extensive legislation reform aimed at improving political competition. We show that, despite these institutional transformations, parliamentary elite maintains informal practices that sustain its reproduction in power, adapting to new institutional conditions. We use biographical data of congressmen (1990 to 2018), as well as original information from interviews to political authorities and experts between 2016 and 2018 in several regions of the country. A growing but moderate diversification of the parliamentary elite has not pushed back informal practices aimed at the co-optation of public resources: they fulfill a coordination role in an environment of low institutional trust, but they also respond to opportunities for control at a time of strong electoral uncertainty. In the end these practices result in greater control of the parliamentary elite over regional and local levels, despite the initial intentions of the reforms. © 2020 Federacion Espanola de Sociologia. All rights reserved.